Assédio moral no âmbito hospitalar: estudo com profissionais de enfermagem - Leite, Alice Iana Tavares (2012)
INTRODUCTION: The moral harassment is occurring frequently in labor relations, setting up as a silent psychological violence and causing damage to the dignity and to the physical and mental integrity of the victim. OBJECTIVES: To investigate the situations of moral harassment experienced by nurses, technicians and nursing assistants in hospitals, to identify the aggressors of nursing professionals and their characteristics; to list the characteristics of the victims of moral harassment; to ascertain the causes of moral harassment among nursing workers in hospital context; and to verify the consequences of moral harassment for the professionals enrolled in the study. METHODOLOGY: This is an exploratory research, with a quantitative approach, developed in a public hospital of João pessoa-PB, with 165 nursing professionals. Data collection occurred in the period from April to July of 2011, through a questionnaire. The empirical material was analyzed quantitatively, using the Program Statistical Package for the Social Sciences (SPSS). RESULTS: Participated in the study 47 nurses, 42 technicians and 76 nursing assistants, predominantly female, mulatto and time working in hospitals over 15 years for the three categories, age group between 50 and 60 years (nurses) and, 30 and 40 years (technicians and assistants). The higher marital status for nurses and assistants was the married, and for the technicians was divided between singles and married. The salary range from two to six minimum wages, for technicians and assistants, and from six to fourteen, for nurses. It was found that 33, 33% of nursing workers were victims of moral harassment at work, mainly the nurse (36, 17%). With regard to situations of moral harassment, the most frequent for the three categories was the one that the aggressor criticized the work in an exaggerated and unfair way, and the exposure time varied from three months to more than ten years. Regarding the aggressor, the nurse was who more practiced the moral harassment and the main character it is always the one who is right, being appointed by the three categories. Concerning the characterization of the moral harassment victims, it was noticed that 94,55% were female; 35,85%, aged between 40 and 50 years; 50,91%, were brown; 47,27%, married; and the prevailing salary range was located between 10 and 14 minimum wages (nurses) and between 2 to 6 (technicians and assistants). With regard to the reason of harassment occurrence, the most pointed out by nurses and assistants was not bowing to the authoritarianism and for the technicians, was to be devoted to work. On the consequences for the victim, were observed behavioral, psychosomatic and psychopathology damages. CONCLUSION: It was possible to see that the moral harassment is present in nursing work, in hospitals, and it leads to disastrous consequences for the health of the victims. In this sense, it is expected that the obtained results from this dissertation can support more investigations on the theme, whose studies are still incipient, and the moral harassment is the most serious threat to the health of the workers to be faced.